Right tracheal sleeve pneumonectomy with VV-ECMO assistance for non-small cell lung cancer through anterior thoracotomy: a single centre experience - Marziali, Valentina; Mangiameli, Giuseppe; Crepaldi, Alessandro; Piccioni, Federico; Costantini, Elena; Citterio, Enrico; Borbone, Alessandro; Cariboni, Umberto (Frontiers in Surgery, 2023)
For a long time, non-small cell lung cancer (NSCLC) arising less than 2 cm distal to the carina have been usually considered unresectable and incurable with a radical or extended resection because surgical technical difficulty and airway management. Recently the introduction of more advanced surgical techniques, often including the use of extracorporeal life support (ECLS), has allowed to extend the limits of conventional surgery increasing the rate of a complete surgical resection. ECLS also overcomes the limitation of conventional ventilation during complex tracheo-bronchial reconstruction avoiding the presence of disturbing lines or tubes that obstruct the operative field during a challenging surgery. In this article we share our experience in performing right tracheal sleeve pneumonectomy with veno-venous extracorporeal membrane oxygenation (VV-ECMO) in three cases by anterior right thoracotomy reporting our tips and tricks.